The Photorhabdus asymbiotica virulence cassettes deliver protein effectors directly into target eukaryotic cells - Vlisidou, Isabella (eLife, 2019)
Photorhabdus is a highly effective insect pathogen and symbiont of insecticidal nematodes. To exert its potent insecticidal effects, it elaborates a myriad of toxins and small molecule effectors. Among these, the Photorhabdus Virulence Cassettes (PVCs) represent an elegant self-contained delivery mechanism for diverse protein toxins. Importantly, these self-contained nanosyringes overcome host cell membrane barriers, and act independently, at a distance from the bacteria itself. In this study, we demonstrate that Pnf, a PVC needle complex associated toxin, is a Rho-GTPase, which acts via deamidation and transglutamination to disrupt the cytoskeleton. TEM and Western blots have shown a physical association between Pnf and its cognate PVC delivery mechanism. We demonstrate that for Pnf to exert its effect, translocation across the cell membrane is absolutely essential.